Pengaruh Good Corporate Governance terhadap Kinerja Keuangan dengan CSR Sebagai Variabel Intervening (Journal of Applied Accounting, 2024)
This study aims to examine the impact of implementing Good Corporate Governance (GCG) principles on financial performance, with Corporate Social Responsibility (CSR) disclosure acting as a mediating variable. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Financial performance is measured using the Return on Assets (ROA) indicator. The audit committee is assessed based on the number of its members, while institutional ownership is evaluated by the percentage of shares owned by institutions relative to the total shares outstanding. CSR disclosure is analysed using the number of items aligned with the Global Reporting Initiative (GRI) standards. The study population consists of 63 companies, from which 25 were selected using a purposive sampling method based on specific criteria. Data were sourced from annual reports available on the IDX and analysed using the Partial Least Square (PLS) method, supported by the WarPLS 8.0 software. The findings reveal that both the audit committee and institutional ownership have a significant positive effect on financial performance. However, CSR disclosure has a significant negative impact on financial performance. Furthermore, the audit committee and institutional ownership significantly and positively influence CSR disclosure. Despite this, CSR disclosure does not mediate the relationship between the audit committee and financial performance, nor between institutional ownership and financial performance. The study underscores the importance of effective corporate governance in enhancing financial outcomes, while also highlighting the need for a more strategic approach to CSR disclosure to create tangible benefits for companies.Keywords: audit committee, institutional ownership, financial performance, corporate social responsibility.